Assessment of Thyroid Profile in Diabetes Mellitus Type 2 Patients at LUMHS, Jamshoro/ Hyderabad - Bai, Kavita; Abbassi, Abdullah; Suthar, Ramesh Kumar; Qasmi, Rasheeda; Bhatti, Urooj; Rani, Keenjhar (Journal of Liaquat University of Medical & Health Sciences, 2021)
Objectives: To assess status of thyroid functions among the type 2 diabetic patients. Methodology: This cross-sectional comparative study conducted in Department of Physiology LUMHS, in collaboration with Diabetic clinic and diagnostic research laboratory of LUMHS, Jamshoro from September 2015 to February 2016 with non-probability sampling technique. The volunteers recruited in the study were one hundred two (n, 102) type 2 diabetic patients and one hundred two (n, 102) non diabetic individuals. Thyroid stimulating hormone (TSH) and thyroid hormones (T3 and T4) were measured using autoanalyzer by Cobas e411, Roche. The data analyzed on SPSS version 16.0 and the p value less than 0.05 were reflected statistically significant. Results: Mean age of study participants was 45.85 years±9.08 in this research study. The mean and standard deviation of T3 among type 2 diabetic and non- diabetic groups were 1.144ng/ml± 0.38 and 1.145ng/ml±0.36 respectively with insignificant difference (p value = 0.98). However, the mean± standard deviation of T4 levels among type 2 diabetic and non- diabetic groups were 7.13 µg/dl±1.95 and 7.33 µg/dl±2.0 respectively with non-significant difference (p value = 0.98). Instead, there was statistically noteworthy difference of TSH between type 2 diabetic and non-diabetic people (p value revealed to be <0.01). Mean ± standard deviation of TSH was 6.42 µU/ml±1.36 and 1.87 µU/ml±1.30 among type 2 diabetic patients and non- diabetic healthy individuals respectively. Thyroid dysfunctions found to be 18% among type 2 DM patients. Conclusion: It has been concluded from this research that there is a significant variance of TSH levels among type 2 diabetic patients and non-diabetic healthy individuals. Key words: Type 2 diabetes mellitus, Non-diabetic healthy individuals, thyroid functions